Pengaruh Model Guided Discovery Terhadap Kesadaran Metakognitif dan Hasil Belajar Kognitif Peserta Didik pada Materi Sistem Reproduksi Manusia di MAS Babun Najah Banda Aceh - Cut Windasari; Hasanuddin Hasanuddin; Hasanuddin Hasanuddin (Biotik, 2016)
This study aimed to figure out the effect of guided discovery model towards metacognitive awareness and cognitive learning outcomes of students in the concept of human reproductive system. This research was conducted at MAS Babun Najah Banda Aceh from April to May 2016. The method used was true experimental with pretest-posttest control group design. The population was all students of four classes namely MIA XI-1, XI MIA-2, XI MIA MIA-3 and XI-4, while the sample were students of two classes of MIA XI-1 and XI MIA MIA-3. The research instruments used were metacognitive awareness inventory sheets and item of cognitive test. The data were analyzed by using independent samples t-test with SPSS 17.0 for windows. The results showed that metacognitive awareness has tcount > t table (3.422> 2.0154), meanwhile, t-test for cognitive learning outcomes also showed tcount > t table (3.089> 2.0154). It can be concluded that guided discovery model affected the increasing of metacognitive awareness and cognitive learning outcomes of students in the human reproductive system concept at MAS Babun Najah Banda Aceh.